PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DI KUSUMA SAHID PRINCE HOTEL : STUDI KASUS DEPARTMENT FRONT OFFICE - Solikhin, Agus; I Gusti Ayu Agung; Kusuma, Dhela (STABN Raden Wijaya Wonogiri, 2024)
The work environment and career development are two interrelated aspects in the context of the professional world of work. Work environment Refers to the physical, social and psychological conditions in the place where a person works. This includes factors such as organizational culture, team dynamics, company values, relationships between employees, well-being, cooperation, and other factors that influence the daily work experience. Meanwhile, career development refers to individual efforts to improve their skills, knowledge and competencies to achieve higher career goals. The impact of career development and work environment on employee performance at the Kusuma Sahid Prince Hotel is covered in this study. The goal of this study is to ascertain and evaluate how career development and work environment affect employees' performance at the Kusuma Sahid Prince Hotel. Qualitative research is the methodology employed. The data gathering techniques used in this study are described later. The study's conclusions are as follows: (1) the work environment positively affects employee performance; and (2) career development positively affects employee performance. The study's findings indicate that front desk personnel' performance is impacted by their work environment and opportunities for career advancement at Kusuma Sahid Prince Hotel Surakarta.